Challenges and experiences of professional development: Perspectives of secondary school principals - Buhle Stella Nhlumayo; Matanki Irene Mabeleng (International Journal of Educational Management and Development Studies)
Principals are entrusted with a significant responsibility to manage schools and encounter numerous challenges in running them effectively, including limited access to ongoing professional development, which hampers their ability to adapt to changing educational demands and lead with confidence. Professional development is critical to succeed in their roles as leaders since it advances their knowledge and enhances their job performance. This qualitative study explored the realities of professional development for secondary school principals in Lesotho. The paper was grounded in the interpretive qualitative paradigm, supported by constructivism, and used phenomenology as a research design. Purposive sampling was used to identify the participants, and semi-structured interviews were conducted with five principals from five secondary schools. Thematic data analysis revealed that principals had a restricted understanding of their professional development programmes, that there was a lack of in-place programmes for school principals, and that they were expected to support professional development programs in their schools. These findings revealed the passive participation of school principals as they still needed to gain skills and knowledge that could enhance their leadership. The study recommends that the Ministry of Education and Training implement structured and continuous leadership development programmes tailored to the practical challenges faced by school principals. These programmes should include mentorship, peer collaboration, and context-specific training modules. Additionally, it is recommended that principals proactively initiate school-based professional development initiatives, such as peer learning communities, in-service workshops, and reflective practice sessions, aligned with their specific leadership and instructional needs.